Uma concepção de bioética na perspectiva evolucionista - Pereira Júnior, Alfredo [UNESP] (My University, 2013)
James Mark Baldwin possibly was the first thinker to explicitly defend a role for consciousness in the Darwinian evolutionary process. When choosing actions with a pleasurable outcome, instead of actions with a painful result - and then contributing for the generation of habits that influence the frequency of distribution of genes in a population - every living being participates in the directioning of the evolutionary process. This proposal has an important consequence for Bioethics, as long as this discipline can be viewed in the broad sense of an "Ethics of Life". When making his/her conscious decisions, every living being, itself a result of the evolutionary process, influences the process. However, this looping is not sufficient to define a bioethical consciousness. Such a modality of consciousness requires more than hedonic choices; it requires intentional actions directed towards admirable goals, tracing a continuity and coherence of the conscious subject in time, which would correspond to what Aristotle called "the virtue of Magnanimity".

James Mark Baldwin talvez tenha sido o primeiro pensador a defender explicitamente um papel da consciência no processo evolutivo darwiniano. Ao optar por uma ação que produza uma reação prazerosa, ao invés de uma ação que produza uma reação dolorosa (e deste modo contribuindo para gerar um novo hábito que venha a influenciar os padrões de reprodução de uma população), todo ser consciente estaria participando na definição dos rumos do processo evolutivo. Essa proposta teria uma consequência importante para a Bioética, no sentido de uma Ética da Vida: ao realizar suas opções conscientes, todo sistema vivo influencia os rumos do processo evolutivo. Entretanto, uma consciência bioética pressupõe mais que escolhas hedônicas; é preciso que hábitos assim formados embasem ações intencionais voltadas a metas admiráveis, ensejando uma coerência do Eu no tempo, o que Aristóteles entendia como sendo a virtude da magnanimidade.
A concept of bioethics in the evolutionary perspective
Keywords: Bioethics; Consciousness; Evolution; Hedonism; Magnanimity; Bioética; Consciência; Evolução; Hedonismo; Magnanimidade